2020
DOI: 10.47067/reads.v6i2.215
|View full text |Cite
|
Sign up to set email alerts
|

An Empirical Study on Students’ Satisfaction from Mawlana Bhashani Science & Technology University, Bangladesh

Abstract: The main motive of this study is to explore university canteen foodservice attributes (food quality, food variety, price fairness, ambience, staff, and student satisfaction)in Mawlana Bhashani Science & Technology. Data are accumulated through a simple random sampling technique. A total of 355 numbers of valid questionnaires is used for statistic exploration. For measuring the performance of all factors for student satisfaction, 7 points Likert Scale is used.Qualitative& quantitative systems are used i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
(17 reference statements)
0
8
0
Order By: Relevance
“…The finding of this study points out food quality as a significant factor that matches with other similar study findings. In a study by some researchers in Bangladesh, focusing on the students' satisfaction, food quality was also found as a significant factor (Akter et al, 2020). Food quality also scored the second most significant factor in another recent study which was focused on the impact of food service attributes on customer satisfaction in a rural university campus environment (Serhan & Serhan, 2019).…”
Section: Hypothesis Testing and Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…The finding of this study points out food quality as a significant factor that matches with other similar study findings. In a study by some researchers in Bangladesh, focusing on the students' satisfaction, food quality was also found as a significant factor (Akter et al, 2020). Food quality also scored the second most significant factor in another recent study which was focused on the impact of food service attributes on customer satisfaction in a rural university campus environment (Serhan & Serhan, 2019).…”
Section: Hypothesis Testing and Discussionmentioning
confidence: 94%
“…To create a good impact and students' satisfaction, food quality is a determining factor. It is considered a vital factor for the satisfaction of university students (Akbara et al, 2021;Akter et al, 2020;Bourne, 2021). The importance of this factor is crucial since it is thought to be a significant factor by a recent study which focuses on fighting non-commutable disease by promoting healthy cafeteria (DK et al, 2020).…”
Section: Food Qualitymentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that job engagement is influenced by the human resources practices and leadership styles in Bangladesh (Akter et al, 2020;Rabiul & Yean, 2021). However, their studies were conducted in the banking sector and hospitality sector.…”
Section: Introductionmentioning
confidence: 99%